Microbiota Differences of the Comb Jelly Mnemiopsis leidyi in Native and Invasive Sub-Populations - Jaspers, Cornelia; Weiland-Bräuer, Nancy; Fischer, Martin A.; Künzel, Sven; Schmitz, Ruth A.; Reusch, Thorsten B. H. (Frontiers in Marine Science, 2019)
The translocation of non-indigenous species around the world, especially in marine systems, is a matter of concern for biodiversity conservation and ecosystem functioning. While specific traits are often recognized to influence the success in the establishment of non-indigenous species, the impact of the associated microbial community for the fitness, performance and invasion success of basal marine metazoans remains vastly unknown. In this study, we compared bacterial composition patterns of the invasive ctenophore Mnemiopsis leidyi in different native and invasive sub-populations along with the genetic structure of the host (polymorphic microsatellite markers). Amplicon sequencing of the 16S rRNA gene (V1-V2 hypervariable regions) revealed that M. leidyi as representative of the phylum Ctenophora, the sister group to all metazoans, harbored a distinct microbiota compared to the ambient seawater, which significantly differed across two major tissues, namely epidermis and gastrodermis. Moreover, we identified significant differences in bacterial community compositions between native and invasive sub-populations of M. leidyi indicating, that the microbiota community is likely influenced by the genotypic background of the host.